On mathematical modelling of synthetic measures - Binderman, Zbigniew; Borkowski, Boleslaw; Kozera, Ryszard; Prokopenya, Alexander; Szczesny, Wieslaw (Mathematical Modelling and Analysis, 2018)
This work deals with some properties of synthetic measures designed to differentiate objects in a multidimensional analysis. The aggregate synthetic measures are discussed here to rank the objects including those validating the concentration spread. The paper shows that currently used various measures (based either on a single or a multiple model object) do not satisfy the necessary conditions requested to be met by a "good" synthetic measure.